A new endemic species of Acanthocereus (Cactaceae) from southern Jalisco, Mexico - González-Zamora, Pedro; Rodríguez-Contreras, Aarón; Sánchez, Daniel (Phytotaxa, 2021)
A new species of Acanthocereus, endemic from southern Jalisco, is described and illustrated. Acanthocereus atropurpureus distinguishes by the diameter of mature stems, presence of low ribs with sinuate margins, dull green stem epidermis turning purple during dry season, and the occurrence of four small central spines. We discuss the morphological differences from other Acanthocereus species and we provide information about its habitat and conservation status.